Characterization of magnetic abrasive particles based Magnetorheological polishing fluid. (2017) - Niranjan, M.S.; Singh, Krishna Pratap; Murtaza, Qasim
Abstract: Magnetic abrasive particles (MAPs) were developed by solid phase sintering method at 1000°C in argon atmosphere. The Magnetorheological (MR) polishing fluid has been synthesized with 45 volume% MAPs and 55 volume% base fluid. The MR polishing fluid was characterized at different current on MCR-301 magnetorheometer and steady state rheograms have been drawn. The flow behavior of MAPs based MR polishing fluid has been compared with flow behavior of unbonded magnetic abrasives based MR polishing fluid at same conditions. The result shows better yield behavior and viscosity of MAPs based MR polishing fluid as compared to unbonded magnetic abrasives based MR polishing fluid.